2010
DOI: 10.1017/s1751731110000819
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of uniformity in pig carcass and meat quality traits

Abstract: The study was carried out to provide information on uniformity of commercial pigs on some of the most important traits determining pork quality: carcass, loin, ham and shoulder weights, fatness, drip loss, pH and colour. Three batches of pigs raised at the same farm and slaughtered at four different dates in the same commercial abattoir were considered. Batches included halothane-free females and castrated males, Duroc and Pietrain sire lines and two slaughter weights, but a common maternal line. The first bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The average CV found herein was slightly greater for the weights of loins versus dressed hams, and BF showed the greatest CV among the investigated traits. This pattern for trait uniformity is consistent with the findings of Alfonso et al (2010), who reported a 3-fold greater CV for BF than for CW, ham weight or loin weight. When the CI of the CV were compared, we did not find any difference in uniformity of investigated traits among the dietary groups.…”
Section: Uniformity Of Carcasses and Primal Cutssupporting
confidence: 90%
See 3 more Smart Citations
“…The average CV found herein was slightly greater for the weights of loins versus dressed hams, and BF showed the greatest CV among the investigated traits. This pattern for trait uniformity is consistent with the findings of Alfonso et al (2010), who reported a 3-fold greater CV for BF than for CW, ham weight or loin weight. When the CI of the CV were compared, we did not find any difference in uniformity of investigated traits among the dietary groups.…”
Section: Uniformity Of Carcasses and Primal Cutssupporting
confidence: 90%
“…Uniformity has been described using the coefficient of variation, likewise in the studies of Alfonso et al (2010), Magowan et al (2007), and Patience et al (2004), and differences in uniformity across the dietary groups were tested by comparing CI of CV (Alfonso et al, 2010). The average CV for CW found in the present study is consistent with that reported for CW of Italian heavy pigs by Virgili et al (2003).…”
Section: Uniformity Of Carcasses and Primal Cutssupporting
confidence: 84%
See 2 more Smart Citations
“…Uniformity is an important factor affecting profitability of the pig industry, and the production of gilts and CM in the same batch decreases carcass uniformity (Alfonso et al, 2010). Female castration uniforms growth and carcass characteristics of a given batch of pigs, facilitating farm management and logistics of transport to the slaughterhouse.…”
Section: Gender and Castrationmentioning
confidence: 99%